The Development of Experimental Setups And Experimental Studies of The Process of Energy-Technological Processing of Wood - Timerbaev N. F. Nail; Safin R. G. Rushan; Ziatdinova D. F. Dilyara; Fomin A. А. Anatoly; Mokhovikov A. A. Aleksey Aleksandrovich (2016, 2016)
Title screen